Formation of polypyrrole/metal hybrid interfacial layer with self-regulation functions via ultrasonication. Issue 3 (1st September 2013) - Andreeva, Olga A.; Andreeva, Daria V.; Cherepanov, Pavel V.; Baidukova, Olga; Skorb, Ekaterina V.
Abstract : The authors proposed a novel method of formation of polymer/metal hybrid interfacial layer with switchable properties by using ultrasonication. Intensive ultrasonication leads to the formation of a rough metal interface and triggers free-radical polymerization of monomers in the interfacial region of metal surface. Thus, polymer layer exhibits excellent adhesion to the bulk metal. The novel concept was demonstrated for polypyrrole/aluminum systems. Hydrophilic/hydrophobic properties and corrosion resistance also due to doping/dedoping of polypyrrole of the interfacial layers can be adjusted based on particular application. The proposed method can serve as a platform for formation of interfaces with self-regulating properties: self-healing, switchable hydrophylicity.